Multi‐interfacial catalyst with spatially defined redox reactions for enhanced pure water photothermal hydrogen production. Issue 6 (27th October 2021) - Zhang, Tianxi; Meng, Fanlu; Gao, Minmin; Ong, Wei Li; Haw, Kok‐Giap; Ding, Tianpeng; Ho, Ghim Wei; Kawi, Sibudjing
Abstract: Photocatalytic overall water splitting is a promising strategy to store abundant solar energy as clean fuel, but recombination of photogenerated carriers is the key factor that reduces the efficiency. Herein, we report multi‐interfacial ternary CoP@ZnIn2 S4 @Co3 O4 photocatalyst with coordinated structural and electronic band coupling to concurrently fulfill spatially decoupled redox centers and modulated electric field. For one, the realization of 3D open framework consists of 2D ZnIn2 S4 nanosheets on 1D CoP co‐catalyst maximizes exposures apart from circumvents aggregation and shielding issues. Another is the spatially defined and selective redox reactions where CoP is designated for proton reduction and Co3 O4 for water oxidation. And finally, constructed type II band structure and p‐n junction facilitates directional charge separation, thereby prohibiting the recombination of charge carrier and also increase the local charge density. Besides, small band gap CoP and Co3 O4 exhibit photothermal effect to further enhance photocatalytic hydrogen production. As a result, the photocatalysts could achieve the respective half reaction and pure water hydrogen evolution rate of 4254 and 145 μmol g −1  h −1 under visible light illumination and further enhance to 10 740 and 308 μmol g −1  h −1 when subjected to full spectrum photoheating. This work presents a promising strategy in designing surface and interfacial dominated photocatalytic system to achieve efficient solar energy to chemical conversion. Abstract : A multi‐interfacial CoP@ZnIn2 S4 @Co3 O4 photocatalyst with spatially defined redox reactions and built‐in electric field was prepared to achieve spontaneous photothermal hydrogen production in pure water. The constructed type II band structure and p‐n junction facilitates directional charge separation, thereby prohibiting the recombination of charge carrier and also increase the local charge density.